Extracellular vesicles as a novel photosensitive drug delivery system for enhanced photodynamic therapy - Tong, Lingjun; Zhang, Sitong; Huang, Rong; Yi, Huaxi; Wang, Jiong-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Photodynamic therapy (PDT) is a promising non-invasive therapeutic approach that utilizes photosensitizers (PSs) to generate highly reactive oxygen species (ROS), including singlet oxygen, for removal of targeted cells. PDT has been proven efficacious for the treatment of several diseases, including cancer, cardiovascular disease, inflammatory bowel disease, and diabetic ocular disease. However, the therapeutic efficacy of PDT is limited and often accompanied by side effects, largely due to non-specific delivery of PSs beyond the desired lesion site. Over the past decade, despite various nanoparticular drug delivery systems developed have markedly improved the treatment efficacy while reducing the off-target effects of PSs, concerns over safety and toxicity of synthetic nanomaterials following intravenous administration are raised. Extracellular vesicles (EVs), a type of nanoparticles released from cells, are emerging as a natural drug delivery system for PSs in light of EV’s potentially low immunogenicity and biocompatibility compared with other nanoparticles. This review aims to provide an overview of the research progress in PS delivery systems and propose EVs an alternative PS delivery system for PDT. Moreover, the challenges and future perspectives of EVs for PS delivery are discussed.